The Influence of Traceability of Kerinci Coffee Agricultural Products on Agricultural Value Added in Jambi Province - Heppi Syofya; Afdhal Chatra P (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this study is to determine the effect of the supply chain of Kerinci coffee agricultural products on the value added of the agricultural economy of Jambi Province. Design/methodology/approach: To improve coffee supply chain performance, innovation is needed through a value added approach between business actors using a transparency approach and supply chain management. Findings: The trend of coffee commodity demand continues to increase with an average value of coffee consumption needs per year of 1.2 kg per capita / year in 2019, even Indonesia is the 3rd largest coffee producer in the world. Research limitations/implications: Along with the increase in people's income, the price factor is no longer the main thing to consider the decision to consume an item. Originality/value: This paper is original Paper type: Research Paper